2017
DOI: 10.1016/j.ymssp.2016.07.018
|View full text |Cite
|
Sign up to set email alerts
|

On the exploitation of mode localization in surface acoustic wave MEMS

Abstract: This work is licensed under a Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International licence Newcastle University ePrints-eprint.ncl.ac.uk

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Sprung et al [163] studied the relationship between bound states and surface states in finite periodic systems. In the last years, the TFPS was successfully applied to calculate optical transitions in the active region of (blue) laser devices, [164,165] to study phonon modes in wurtzite, [166] periodic structures, coupled resonators and surface acoustic waves for mode localization sensors, [167] to adjust the coherent transport in finite periodic SLs, [168] transport through ultrathin topological insulator films, [169] to model QW solar cells, [170] to study the expectation values for Bloch functions in finite domains, [171] bound states in the continuum, [172] wave packets (WPs) on finite lattices and through semiconductor and optical-media SLs, [173][174][175][176] to calculate the magneto-conductance of cylindrical wires in longitudinal magnetic fields, [177] persistent currents in small quantum rings, [178] spin transport through magnetic SLs, [103,105,106,108,179] to explain the spin injection through Esaki barriers in ferromagnetic/nonmagnetic structures, [85,[180][181][182][183][184] to study properties of metamaterial SLs and the antimatter effect, [185,186] to improve the theoretical approach to study electromagnetic waves through fiber Bragg gratings, [187] to show why the effective mass approximation works well in nanoscopic structures, [188] and many other physical properties and systems.…”
Section: Introductionmentioning
confidence: 99%
“…Sprung et al [163] studied the relationship between bound states and surface states in finite periodic systems. In the last years, the TFPS was successfully applied to calculate optical transitions in the active region of (blue) laser devices, [164,165] to study phonon modes in wurtzite, [166] periodic structures, coupled resonators and surface acoustic waves for mode localization sensors, [167] to adjust the coherent transport in finite periodic SLs, [168] transport through ultrathin topological insulator films, [169] to model QW solar cells, [170] to study the expectation values for Bloch functions in finite domains, [171] bound states in the continuum, [172] wave packets (WPs) on finite lattices and through semiconductor and optical-media SLs, [173][174][175][176] to calculate the magneto-conductance of cylindrical wires in longitudinal magnetic fields, [177] persistent currents in small quantum rings, [178] spin transport through magnetic SLs, [103,105,106,108,179] to explain the spin injection through Esaki barriers in ferromagnetic/nonmagnetic structures, [85,[180][181][182][183][184] to study properties of metamaterial SLs and the antimatter effect, [185,186] to improve the theoretical approach to study electromagnetic waves through fiber Bragg gratings, [187] to show why the effective mass approximation works well in nanoscopic structures, [188] and many other physical properties and systems.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a growing interest in the development of MEMS devices based on Anderson mode localization to increase the sensitivity to mass perturbation in the last decade [1][2][3][4][5][6][7]. Mode localization occurs within an array of weakly coupled identical resonators in which a mass or stiffness perturbation is introduced.…”
Section: Introductionmentioning
confidence: 99%
“…Chellasivalingam, et al [20] reported a Q-factor of 2400 in air and reached a 367.8-pg resolution with amplitude ratio of the coupled piezoelectric resonators as readout metric. Hanley et al [21] and Humbert et al [22] also proposed solutions of mode-localized mass sensors for highperformance mass sensing. To accurately monitor the resonant frequency and amplitude of the mode-localized sensors in real-time, phase-locked loop (PLL) and proportional-integralderivative (PID) controller modules are normally required for capacitive resonators [23], which significantly increases the systematic complexity.…”
mentioning
confidence: 99%